Curcumin – Pharmacological Actions And its Role in Oral Submucous Fibrosis: A Review - Alok, Abhijeet (J Clin Diagn Res, 2015)
Turmeric has been in use for thousands of years as a dye, flavouring and a medicinal herb. Ancient Indian medicine has touted turmeric as an herb with the ability to provide glow and lustre to the skin as well as vigour and vitality to the entire body. Since curcumin has antimicrobial, antioxidant, astringents and other useful properties, it is quite useful in dentistry also. Curcumin, the most active polyphenolic constituent, is the active ingredient in the traditional herbal remedy and dietary spice turmeric. In gel form it is a component in local drugs delivery system. The objective of this article is to review the pharmacological action of turmeric and its use in treating oral submucous fibrosis.